Electrochemical Determination of Inorganic Contaminants in Automotive Fuels - Santos, Andre L.; Takeuchi, Regina M.; Munoz, Rodrigo A. A.; Angnes, Lucio; Stradiotto, Nelson Ramos [UNESP] (Wiley-v C H Verlag Gmbh, 2012)
This article critically reviews the electroanalytical methods developed for the determination of inorganic contaminants in automotive fuels. Topics include the methods applied to the analysis of liquid biofuels and liquid fossil fuels for which different strategies were developed based on analytes and sample matrices. Special attention is given to electrodes, detection techniques, and sample preparation protocols (when required). Analytes include anions such as chloride, sulfate and phosphate, and mainly metallic species such as sodium, potassium, magnesium, calcium, cadmium, copper, iron, lead, manganese, mercury, nickel, platinum, tin, vanadium, and zinc. Suggestions for future research are also presented.
Keywords: Biodiesel; Bioethanol; Gasoline; Inorganic species; Electrochemical methods